Why Land Here? Ports and Harbors in Southeast Tanzania in the Early Second Millennium AD. (2nd October 2017) - Pollard, Edward; Ichumbaki, Elgidius B.
ABSTRACT: The east African Swahili ports developed extensive maritime trading links around the Indian Ocean, and supported economic, political, and urban growth in the early second millennium AD. This article identifies ports of varying function and importance in SE Tanzania, and seeks to understand their development in the context of natural harbor advantage, boat technology, sailing practice, and resource needs. Field data from landing places are combined with weather patterns, historical documents, and oral traditions to provide an integrated survey of the ports and harbors that once sustained medieval commerce along this section of the Swahili coast. The emergence of Kilwa as an entrepôt to become the key center is based initially upon its naturally advantageous harbor facilities, safety and flexibility of approach in days of sail, and assurance of monsoon winds. Original natural advantages gradually become self-sustaining with its economic and political growth. To the north and south of Kilwa a series of ports of call with drinking water and boat servicing supported trade to and from the pre-eminent city, although some such as Kisimani Mafia and Kwale-Kisuju developed important trade functions of their own.